How do bankruptcy laws affect entrepreneurship development around the world? - Lee, S.; Yamakawa, Y.; Peng, Mike; Barney, J. (2011)
How do bankruptcy laws as formal institutions affect entrepreneurship development around the world? Do entrepreneur-friendly bankruptcy laws encourage more entrepreneurship development at a societal level? We posit that if bankrupt entrepreneurs are excessively punished for failure, they may give up potentially high-return but inherently high-risk opportunities to start new businesses. Amassing a cross-country database from 29 countries spanning 19. years (1990-2008), we find that lenient, entrepreneur-friendly bankruptcy laws are significantly correlated with the level of entrepreneurship development as measured by the rate of new firm entry.